Development of object model of the generalized configuration management process in project management - Рудницкий, Сергей Иванович (Technology audit and production reserves, 2015)
Almost inevitable changes in external and internal environment of the project leads to the problem of consistency support the project and its results, i.e. the product of the project. The essence of the problem lies in the fact that the lack of control over changes to the object, the values of the characteristics which cause the values of the characteristics of other objects can lead to mismatch of characteristic values of dependent objects. Because of this mismatch may be exceeded or completion dates of the project budget. In this investigation it is developed a mathematical model of the object of the process of the configuration management – the model of controlled object. A feature of this model is its versatility in relation to the kind of object. So, using the presented model, it can be formalized both tangible and intangible objects controlled by the process of the configuration management. The underlying concepts of configuration management sector are mathematically described. Such concepts are: characteristics, current and consistent state characteristics, specifications change, consistency relation, object, current and consistent state of the object, changing the subject. It is identified and described the mathematical object "object consistency map", which is a directed graph built on the binary relations, reflecting the ratio of consistency between the characteristics of the controlled object, and those characteristics that affect the consistency of the object. The results can be used to develop a mathematical model of configuration management of an object and its further optimization for efficient implementation.